LUTHER AND LUTHERANISM: THE P. O. BOX MARTIN LUTHER - Marco Ornelas (European Scientific Journal, ESJ, 2013)
This article explores the idea that social communication performs coupled with the consciousness of human beings –but it is not generated by it, and gives the example of the German reformer Martin Luther. An overlap in the operations of consciousness and of communication – interpenetration- is made possible with the person/actor distinction, which actualizes in communication through schemas (the person-schema and the actor-schema), the so called P. O. Box Martin Luther. Luther’s positioning in relation to the polemical controversies in which he participated –the Peasants’ War (radical Anabaptism), the free will, and the sacramental debate-, determined the future course of his Reform, and was decisively oriented by the person-schema. The person/actor schemas also allow the distinction between Luther the person and Lutheranism the doctrine.